Total ıntravenous anesthesıa wıth spontaneous breathıng for transvagınal oocyte retrıeval - Göğüs, Yılmaz; Yaycı, Abdurrahman; Eti, Zeynep (My University, 2002)
Objective: The aim of this study was to compare the adequacy of spontaneous breathing and assisted ventilation with laryngeal mask airway (LMA) during total intravenous anesthesia for transvaginal oocyte retrieval. Methods: One hundred patients, undergoing transvaginal oocyte retrieval under propofol - alfentanil anesthesia were randomly assigned into two groups. Anesthesia was induced with 2 mg.kg-1 propofol and 10 pg.kg-1 alfentanil i.v. in all patients . The ventilation was assisted with LMA in group I and was spontaneous in group II. One mg.kg-1 propofol and 5 pg.kg-1 alfentanil i.v. were administered when needed. Systolic and diastolic blood pressure, heart rate, oxygen saturation (Sp02) and end-tidal C02 pressure (ETC02), total drug doses administered, side effects and Aldrete recovery score were recorded. Results: Blood pressure and heart rate decreased significantly in all patients after induction (p<0.001). Sp02 increased and ETC02 decreased significantly at the 5th min in group I. Sp02 in group I and ETC02 in group II was found significantly higher (p<0.001) but remained within normal range during the operation. There were no differences in the time to achieve an Aldrete recovery score of 10 and the incidence of side effects. Conclusion: We concluded that propofol- alfentanil anesthesia with spontaneous breathing is an effective and safe anesthetic technique for transvaginal oocyte retrieval.
Keywords: Intravenous anaesthetics, Propofol, Alfentanil, Transvaginal oocyte retrieval